2020
DOI: 10.3389/fphar.2020.551683
|View full text |Cite
|
Sign up to set email alerts
|

Onion Bulb Extract Downregulates EGFR/ERK1/2/AKT Signaling Pathway and Synergizes With Steroids to Inhibit Allergic Inflammation

Abstract: The treatment of allergic diseases, such as asthma, with both conventional and novel therapies presents a challenge both in terms of optimal effect and cost. On the other hand, traditional therapies utilizing natural products such as onion have been in use for centuries with demonstrated efficacy and safety but without much knowledge of their mechanims of action. In this study, we investigated if the anti-inflammatory effects of onion bulb extract (OBE) are mediated via the modulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 70 publications
(89 reference statements)
2
21
0
Order By: Relevance
“…In the allergic asthma model, our findings showed that OBE, administered 1 h prior to allergen challenge, significantly inhibited the allergen-induced increase in airway cellularity and histopathological changes, and also pro-inflammatory Th2 cytokines such as IL-4 and IL-5 but interestingly enhanced the levels of the anti-inflammatory cytokine IL-10 (El-Hashim et al. 2020 ). We also demonstrated that OBE inhibited the EGFR-dependent signaling pathways (El-Hashim et al.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the allergic asthma model, our findings showed that OBE, administered 1 h prior to allergen challenge, significantly inhibited the allergen-induced increase in airway cellularity and histopathological changes, and also pro-inflammatory Th2 cytokines such as IL-4 and IL-5 but interestingly enhanced the levels of the anti-inflammatory cytokine IL-10 (El-Hashim et al. 2020 ). We also demonstrated that OBE inhibited the EGFR-dependent signaling pathways (El-Hashim et al.…”
Section: Introductionmentioning
confidence: 81%
“… 2019 ; El-Hashim et al. 2020 ), and also reverses established bowel inflammation (Khajah et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…39,47 In several studies, onion and its bioactive components reduced inflammation in the lungs and protected against various respiratory illnesses. [48][49][50] It is suggested that phytochemicals derived from onions can interfere with the function of the main protease of SARS-CoV-2. [51][52][53] In addition, anti-inflammatory diets that incorporate onions were recommended to reduce the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…They owe their medicinal properties to the presence of a wide range of bioactive compounds (Teshika et al, 2019). Over the years, studies have demonstrated the outstanding health benefits of onion as well as their bioactive compounds including anticancer (Tsuboki et al, 2016), antidiabetic (Jini & Sharmila, 2020), antimicrobial (Loredana et al, 2019), anti‐inflammatory (Jakaria et al, 2019), antiobesity (Lee et al, 2016), antioxidant (Ouyang et al, 2018), cardiovascular protective (Colina‐Coca et al, 2017), digestive system protective (Khajah et al, 2020), hepatorenal protective (Ahmed et al, 2017), immunomodulatory properties (Alkhedaide et al, 2017), neuroprotective (Salami et al, 2020), respiratory protective (El‐Hashim et al, 2020), and reproductive protective (Table 1) (Shokoohi et al, 2018).…”
Section: Bioactive Compounds and Potential Health‐promoting Propertie...mentioning
confidence: 99%